73.1k views
1 vote
Please help!! Please give step by step so i can understand

Find p in the equation ( attached photo of the equation)

Please help!! Please give step by step so i can understand Find p in the equation-example-1
User Jim Fell
by
5.2k points

1 Answer

2 votes

Answer:

p = - 14

Explanation:

Using the rules of exponents


a^(m) ÷
a^(n) =
a^((m-n))


(a^(m)) ^(n) =
a^(mn)

Note 81 = 9² and 729 = 9³

Given


(81)^(-4) ÷
(729)^(2-p)

=
(9^(2)) ^(-4) ÷
(9^(3)) ^(2-p)

=
9^(-8) ÷
9^(6-3p)

=
9^(-8-(6-3p))

=
9^(-8-6+3p)

=
9^(3p-14)

Thus


9^(3p-14) =
9^(4p)

Since bases on both sides are equal then equate the exponents

4p = 3p - 14 ( subtract 3p from both sides )

p = - 14

User Mezzodrinker
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.